Water and nitrogen utilization and growth simulation of soybean-maize strip intercropping: A review /Utilizacao de agua e nitrogenio e simulacao de crescimento do consorcio de tiras de soja-milho: Uma revisao - Wang, Xiaowen; Li, Yalong; Jia, Weidong (Revista brasileira de engenharia agrícola e ambiental, 2025)
As a consequence of rapid population growth and pronounced changes in global climate, food production faces unprecedented challenges, diversified cropping systems have become a key approach for addressing food crises. Rational intercropping, via niche complementarity and interspecific facilitation, enhance resource utilization efficiency, improve the rhizosphere environment, promote diversification of soil microbial communities, and ultimately contribute to increases in crop yields. In this context, soybean-maize strip intercropping has evolved from traditional intercropping practices. This planting pattern fully exploits the specific characteristics of the two crops, thereby contributing to an enhancement of their complementary effects regarding nitrogen utilization, and highlighting the agricultural, environmental, and socioeconomic advantages of this system compared with monoculture production. Consequently, this system of cultivation has been widely applied in production practices in multiple regions globally. In this review, we systematically summarize the water and nitrogen competition patterns, and describe the applicability of modeling in the development of intercropping systems, on the basis of which we identify further key research areas that could contribute to enhancing the benefits of intercropping. Our findings indicate that in the soybean-maize intercropping system, maize has a competitive advantage in terms of water and nitrogen uptake, although there is currently a lack of consensus regarding the spatial distribution characteristics of soybean and maize roots under heterogeneous water and nitrogen conditions. Additionally, the intercropping models proposed to date are primarily based on assessments of interspecific competition via aboveground light interception, whereas belowground resource utilization processes remain insufficiently assessed. Key words: soybean-maize strip intercropping, interspecific competition, crop plasticity, resource utilization, crop growth model No contexto de rapido crescimento populacional e mudancas climaticas drasticas, a producao global de alimentos enfrenta desafios sem precedentes. Padroes diversificados de plantio tornaram-se uma das principais abordagens para enfrentar a crise alimentar. O consorcio razoavel, atraves da complementaridade de nichos ecologicos e promocao interespecifica, e benefico para que as culturas utilizem melhor nutrientes, agua e luz, melhorem a produtividade da terra e eficiencia na utilizacao de recursos, promovam a diversidade microbiana da comunidade do solo, melhorando o ambiente rizosferico e, finalmente, aumentem a produtividade das culturas. O consorcio de tiras de soja e milho evoluiu a partir de praticas consorciadas tradicionais. Esse padrao de plantio aproveita plenamente as caracteristicas de nicho das duas culturas, potencializando seus efeitos complementares na utilizacao de nitrogenio, demonstrando vantagens agricolas, ambientais e socioeconomicas em relacao as monoculturas, e tem sido amplamente aplicado em praticas produtivas em varias regioes do mundo. Os resultados indicam que o milho esta em posicao dominante na competicao hidrica e nitrogenada no sistema consorciado de milho e soja, enquanto as caracteristicas de distribuicao espacial de raizes de soja e milho sob condicoes heterogeneas de agua e nitrogenio ainda sao controversas. Alem disso, os modelos de culturas consorciadas existentes refletem principalmente a competicao interespecifica atraves da interceptacao de energia luminosa acima do solo, carecendo de uma descricao abrangente do processo de utilizacao dos recursos subterraneos. Palavras-chave: consorcio soja-milho, competicao interespecifica, plasticidade da cultura, utilizacao dos recursos, modelo de crescimento da cultura